Friends in need: The corona pandemic changes the landscape and groups and coalitions in the EU - Kai-Olaf Lang; Nicolai von Ondarza (Stiftung Wissenschaft und Politik (SWP), 2020)
The corona pandemic and its economic and social consequences are testing EU cohesion as well as the balance of power in the Union. The belated - or lack of - reaction by the EU during the crisis has reinforced the national sovereignty of the member states and the dominance of the intergovernmental method in moments of crisis. One of the palpable consequences has been an alteration in the 'North-South divide' resulting from a European policy offensive by Spain and Italy, a stronger 'southern orientation' by France, and a simultaneous crumbling of the 'New Hanseatic League'. During the corona crisis, institutionalised groups of member states have acted primarily as interest groups that exacerbate differences rather than overcome them. Germany, which will assume a special mediating role as the Presidency of the Council from 1 July 2020, has to act as a bridge builder.
Keywords: 320